The Changing Role of the Management Accountants Becoming a Business Partner - Chotiyanon, Panida (Springer International Publishing, 2018)
This book presents a comprehensive and holistic study on being a financial practitioner today. Using a practice theory approach, the book analyzes the work life stories of four financial practitioners who have been working between 13 and 25 years during the period of 1973 to 2015 and explains how their work identities are constituted in the practices throughout the years. It clarifies the public image of the management accountants and provides a better understanding of today's management accountants-who they are and how they are formed-while theorizing on how to develop the next generation.